Mitigating membership inference attacks via weighted smoothing - TAN, Minghan (Institutional Knowledge at Singapore Management University, 2023)
Recent advancements in deep learning have spotlighted a crucial privacy vulnerability to membership inference attack (MIA), where adversaries can determine if specific data was present in a training set, thus potentially revealing sensitive information. In this paper, we introduce a technique, weighted smoothing (WS), to mitigate MIA risks. Our approach is anchored on the observation that training samples differ in their vulnerability to MIA, primarily based on their distance to clusters of similar samples. The intuition is clusters will make model predictions more confident and increase MIA risks. Thus WS strategically introduces noise to training samples, depending on whether they are near a cluster or isolated. We evaluate WS against MIAs on multiple benchmark datasets and model architectures, demonstrating its effectiveness. We publish code at https://github.com/BennyTMT/weighted-smoothing.